Spinal Anesthesia in Patients Using Regularly CAT (Catha Edulis Forskal) - M. Nuzeili; N. Ye. Burov; V. N. Marinchev; J. Horeibi (Общая реаниматология, 2009)
Objective: to study the course of spinal anesthesia in regular users of CAT (Catha edulis Forskal). Subjects and methods. The course of spinal anesthesia was studied in 75 patients in relation to the degree of drug dependence in patients with a national habit to chew systematically CAT, the herbal psychogenic stimulant (pseudoephedrine, amphetamine). According to the dependence and clinical manifestations, all the patients were divided into 3 groups. Results. During spinal anesthesia, arterial hypotension and tachycardia were more common in Group 1 and control patients. Groups 2 and 3 patients with baseline hypertonus of the sympathetic nervous system showed a more significant resistance of indices at this stage and virtually needed no ephedrine administration. The time course of changes in the Cardo autonomic index practically corroborated this regularity. However, in the immediate postoperative period, Group 3 patients’ condition is characterized by the signs of functionally exhausted tone of the sympathetic nervous system, as appear as the signs of discomfort, withdrawal syndrome, respiratory and circulatory disorders, urinary retention, enteroparesis, which require active therapy in an intensive care unit. Thus, Groups 2 and 3 patients have a false temporary intraoperative resistance of hemodynamic parameters and psychoemotional status, which are more dramatically observed in the postoperative period. Key words: spinal analgesia, CAT as a psychogenic stimulant, amphetamine, pseudoephedrine, withdrawal syndrome.